2017
DOI: 10.18632/oncotarget.18987
|View full text |Cite
|
Sign up to set email alerts
|

The autophagic inhibition oral squamous cell carcinoma cancer growth of 16-hydroxy-cleroda-3,14-dine-15,16-olide

Abstract: 16-hydroxycleroda-3, 13-dine-15, 16-olide (HCD) isolated from Polyalthia longifolia possesses numerous biological activities. Previous studies have reported that HCD can block phosphorylation activity of cancer cells to inhibit tumor cell growth, but the anti-tumor activity in oral squamous cell carcinoma is unrevealed. This study investigates the inhibiting effect of HCD on human OSCC cell growth; thereby, developing a new oral cancer drug. In in vitro cultured human OSCC cells (OECM1 and SAS) were employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 65 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…In our previous study, HCD was demonstrated to be a non-toxic agent to normal cells [16]. When compared to 5-FU, the cytotoxicity of HCD against colorectal cancer was higher than 5-FU (4.10 vs. 100 µM in IC 50 at 36 h treatment), suggesting that HCD had higher efficacy and more potent when applied to colon cancer treatments.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In our previous study, HCD was demonstrated to be a non-toxic agent to normal cells [16]. When compared to 5-FU, the cytotoxicity of HCD against colorectal cancer was higher than 5-FU (4.10 vs. 100 µM in IC 50 at 36 h treatment), suggesting that HCD had higher efficacy and more potent when applied to colon cancer treatments.…”
Section: Discussionmentioning
confidence: 95%
“…injected once every three days until day 65. Mice were sacrificed by CO 2 anesthesia, and their colons were collected for slicing in the literature [16].…”
Section: Inflammatory Bowel Disease Model Induction and Hcd Treatmentmentioning
confidence: 99%
See 3 more Smart Citations